9.8k views
3 votes
! if f( n + 1) = f(n) + 2 and f(2) = 4 then f(4) =

explain

User Sravan
by
6.4k points

1 Answer

3 votes

Answer: 8

Explanation:

From our knowledge, we know two things.

  • f(n + 1) = f(n) + 2
  • f(2) = 4

From here, we can work out what f(3) is by substituting n as 2

f(2 + 1) = f(2) + 2

f(3) = 4 + 2 = 6

And we can work out f(4) by substituting n as 3

f(3 + 1) = f(3) + 2

f(4) = 6 + 2 = 8

Eventually, if you continue doing this, you will see a sequence forming where the next number is the previous number added by 2.

User SilverHorn
by
6.1k points